2013
DOI: 10.2341/12-084-l
|View full text |Cite
|
Sign up to set email alerts
|

Resin-based Composite Light-cured Properties Assessed by Laboratory Standards and Simulated Clinical Conditions

Abstract: The irradiation technique, used to measure mechanical properties of resin-based composites according to international standards, consistently differs from clinically simulated conditions, calling into question whether laboratory findings can be unrestrictedly applied clinically, especially at short polymerization times. The study analyzes whether degree of conversion measurements at short post-polymerization time (five minutes) are able to predict the long-term material behavior. SUMMARYThe following parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…The probable explanation is that, despite the PE protocol delivering an extremely high energy (3200 mW/cm 2 ), it promoted a rapid initiation of polymerization, inducing to shorter chain lengths and, hence, leading to a lower molecular weight, compromising the hardness of the bottom surface. This behavior is similar to observe for plasma arc curing units [18] and for short polymerization times of 5 or 10 s, even for high-powered LED LCUs [8].…”
Section: First Layered Composite Incrementsupporting
confidence: 76%
See 2 more Smart Citations
“…The probable explanation is that, despite the PE protocol delivering an extremely high energy (3200 mW/cm 2 ), it promoted a rapid initiation of polymerization, inducing to shorter chain lengths and, hence, leading to a lower molecular weight, compromising the hardness of the bottom surface. This behavior is similar to observe for plasma arc curing units [18] and for short polymerization times of 5 or 10 s, even for high-powered LED LCUs [8].…”
Section: First Layered Composite Incrementsupporting
confidence: 76%
“…They last significantly longer and their power of density does not decrease with time. Some high-powered LED LCU manufacturers suggested short polymerization times of up to 5 s [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that the mechanical properties of IPS Empress Direct Trans Opal were lower than those of Dentin shade 28) . It was also shown that IPS Empress Direct Trans Opal had below-average macro-mechanical properties when compared to other nanohybrid RBCs; its mechanical properties were more comparable to those of microfilled RBCs, flowable RBCs and compomers 29,30) .…”
Section: Effects Of Materials Compositionmentioning
confidence: 92%
“…Nevertheless, LED technology has two main drawbacks: First, because first‐ and second‐generation LEDs emit light matching the absorption spectrum of camphorquinone (430–500 nm), they may not provide adequate curing of composite resins containing alternative initiators. Second, the manufacturers of LED units recommend irradiation times of 20 s and 40 s, whereas shorter curing times are always preferable in clinical conditions. In an attempt to overcome these problems, so‐called ‘third‐generation’ LED curing units with multiple diodes and dual emission peaks have been introduced.…”
Section: Introductionmentioning
confidence: 99%